1994
DOI: 10.1002/j.2161-1912.1994.tb00241.x
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic Minority Psychologists: Whom They Mentor and Benefits They Derive From the Process

Abstract: Ethnic minority psychologists were found to be prolific mentors of both ethnic minority and European American proteges. Mentoring benefits were not related to ethnic similarity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
34
1

Year Published

2002
2002
2009
2009

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 17 publications
2
34
1
Order By: Relevance
“…Research on the prevalence of graduate school mentorships in the field of psychology confirms that between one half and two thirds of doctoral students are mentored by faculty (Atkinson, Casas, & Neville, 1994;Clark et al, 2000;Cronan-Hillix et al, 1986;Johnson, Koch, et al, 2000;Kirchner, 1969;Mintz, Bartels, & Rideout, 1995;Swerdlik & Bardon, 1988). Since 1945, clinical psychology doctoral students have been significantly less likely (53%) than nonclinical (experimental) doctoral students (69%) to be mentored (Johnson, Koch, et al, 2000), and among recent clinical psychology graduates, PsyDs (56%) are significantly less likely than PhDs (73%) to be mentored (Clark et al, 2000).…”
Section: How Prevalent Is Mentoring In Psychology?mentioning
confidence: 99%
“…Research on the prevalence of graduate school mentorships in the field of psychology confirms that between one half and two thirds of doctoral students are mentored by faculty (Atkinson, Casas, & Neville, 1994;Clark et al, 2000;Cronan-Hillix et al, 1986;Johnson, Koch, et al, 2000;Kirchner, 1969;Mintz, Bartels, & Rideout, 1995;Swerdlik & Bardon, 1988). Since 1945, clinical psychology doctoral students have been significantly less likely (53%) than nonclinical (experimental) doctoral students (69%) to be mentored (Johnson, Koch, et al, 2000), and among recent clinical psychology graduates, PsyDs (56%) are significantly less likely than PhDs (73%) to be mentored (Clark et al, 2000).…”
Section: How Prevalent Is Mentoring In Psychology?mentioning
confidence: 99%
“…If this trend holds true for other disciplines, then it appears critical for all academics to know how mentoring relationships for nontraditional students differ from those relationships with a traditional student, as well as knowing how to mentor nontraditional and traditional students with equal effectiveness. This latter issue is especially important because the extant research (e.g., Atkinson et al, 1994;Pope-Davis et al, 1997;Schlosser et al, 2005) suggests that mentoring experiences are different for those in socially-privileged groups (e.g., Whites, men, Christians, heterosexuals) than those in socially-oppressed groups (e.g., People of Color, women, LGBT persons, religious minorities). Finally, we also know that the presence (or absence) of mentors of color is an important variable in the professional development of psychology doctoral students of color (Pope-Davis et al, 1997).…”
Section: Mentoring and Noncognitive Variablesmentioning
confidence: 99%
“…Within academia, student-faculty relationships tend to be more formalized, with the most common type being the advisor-advisee relationship in graduate school (Schlosser & Gelso, 2001;Schlosser, Knox, Moskovitz, & Hill, 2003;Schlosser, Talleyrand, Lyons, Kim, & Johnson, 2005). Research has shown that students almost always have an advisor (Schlosser & Gelso, 2001), but only 50 to 66 percent report having a mentor (Atkinson, Casas, & Neville, 1994;Clark, Harden, & Johnson, 2000;Cronan-Hillix, Davidson, Cronan-Hillix, & Gensheimer, 1986;Hollingsworth & Fassinger, 2002;Johnson, Koch, Fallow, & Huwe, 2000). So, while our focus is on mentoring, it is important to note that many mentors are also advisors, and researchers have speculated that positive advising relationships and mentoring relationships are quite similar (Schlosser & Gelso, 2001;Schlosser & Gelso, in press).…”
mentioning
confidence: 99%
“…For example, although women now make up the majority of psychology graduate students, most faculty members, particularly senior faculty are men (Cohen & Gutek, 1991;Cronan-Hillix et al, 1986;Pion et al, 1996). Similarly, while the number of ethnic minority students in (Pion, 1996) the numbers are still very small (APA, 2008;Atkinson, Casas, & Neville, 1994). Some have reported that women and minority students typically have less access to mentoring and that good mentoring may help them gain advantages more frequently afforded to members of majority groups (Bogat & Redner, 1985;Cohen & Gutek, 1991;Gilbert & Rossman, 1992;Wilson & Johnson, 2001).…”
mentioning
confidence: 99%